If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 3 = x + 13 Reorder the terms: 3 + 7x = x + 13 Reorder the terms: 3 + 7x = 13 + x Solving 3 + 7x = 13 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 3 + 7x + -1x = 13 + x + -1x Combine like terms: 7x + -1x = 6x 3 + 6x = 13 + x + -1x Combine like terms: x + -1x = 0 3 + 6x = 13 + 0 3 + 6x = 13 Add '-3' to each side of the equation. 3 + -3 + 6x = 13 + -3 Combine like terms: 3 + -3 = 0 0 + 6x = 13 + -3 6x = 13 + -3 Combine like terms: 13 + -3 = 10 6x = 10 Divide each side by '6'. x = 1.666666667 Simplifying x = 1.666666667
| -2=6(p-1)-4(3+p) | | 5(b+1)=2b+32 | | 2-4x=38 | | 5.3y+0.45=3.02y-2.04 | | 2x+49=-6x+97 | | (2x+4)(6x-8)= | | 8x+70=9x+69 | | 2y-6x=-3 | | 7K+3=K+13 | | 3y-4(-4y-18)=-118 | | 2/3+2=4/3+1/3 | | 19=.8(20x+16)-14x | | 1.05p=31.5 | | 20w+100=280 | | 2d^2+7d=0 | | 6v(2v-3)= | | 4q-72=q+24 | | 13+6z=7(z-1) | | 3(4x-9)=29 | | 4x^3+12x^2+16=0 | | 3c+47=9c+41 | | 4(5)+y=24 | | 100y-2x=0 | | 15b=7b+40 | | 3p-1-2x+9=0 | | 19t+31=2t+65 | | r^2=88 | | 6h+8=26 | | 10y-2x=5 | | -1[7x+6(x+1)]=-4x-6 | | 2y-30=3y-54 | | (11x-25)+(24+10)=90 |